PENGARUH SELF-EFFICACYDAN MOTIVASI KERJA PADA KEPUASAN KERJA KARYAWAN HAPPY BALI TOUR & TRAVEL DENPASAR - Putu Eka Purnama, Dewi; I Gusti Ayu Manuati, Dewi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 9 Nomor 1 Tahun 2015, 2015)
The aim of this study is to determine the influence of self-efficacy and work motivation on employee job satisfaction at Happy Bali Tour and Travel. The data was collected by using questionnaire consisting of a number of statements about self-efficacy, motivation and job satisfaction. This study used saturated sample, where the entire population was selected become sample which is consists of 82 employees. Data analysis techniques used in this research was multiple linear regression. The findings show that simultaneously,  self-efficacy  and  work  motivation  has  a  significant  effect  on  job  satisfaction  of employee. Additionally, self-efficacy and work motivation shows a positive impact on job satisfaction of Happy Bali Tour and Travel employee.
Keywords: job satisfaction, work motivation, self-efficacy